Pengendalian Biaya Bahan Baku Pada PG XYZ Di Jawa Timur - Varomah Wati; Anita Handayani (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the control of raw material costs carried out by the company in covering the costs of losses that occur. The type of research used is descriptive qualitative research. The research techniques used are interviews and direct observation of the head of the People's Sugar Cane Administration (ATR). Sugarcane is the main raw material for making sugar. Sugarcane obtained by PG XYZ does not come from just one place. PG XYZ gets sugarcane raw materials by establishing partnerships with farmers. However, not all raw materials that meet physical standards are accepted by PG XYZ. In one month ± the cost loss borne by the company amounted to Rp 26,000,000 / month. Where the company has to spend money to cover existing cost losses by refining raw materials that do not pass the physical standards of information from the head of the ATR section.